Peculiarities of legal requirements for notarial acts connected with protection of inheritance rights - Філик, Наталя Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article investigates peculiarities of certain notarial acts in accordance with current legislation by wayof example of inheritance relationships.